Snoring and carotid artery disease: A new risk factor emerges. (8th September 2018) - Deeb, Robert; Smeds, Matthew R.; Bath, Jonathan; Peterson, Edward; Roberts, Matthew; Beckman, Nanette; Lin, Judith C.; Yaremchuk, Kathleen
Abstract : Objectives/Hypothesis: Previous studies have identified a relationship between snoring, carotid intima media thickening, and the presence of atherosclerosis. This study examines the correlation between snoring and carotid artery disease through use of duplex ultrasound identifying greater than 50% internal carotid artery stenosis. Study Design: Prospective cohort study. Methods: Patients presenting to three academic vascular laboratories for carotid duplex examination completed the following surveys: demographic information, assessment of risk factors for carotid stenosis, assessment of history of obstructive sleep apnea, or continuous positive airway pressure use and Snoring Outcomes Survey. Patients were categorized into 2 groups based on the presence or absence of carotid disease. Data were analyzed by univariate contingency tables and logistic regression analysis. Results: Five hundred one patients completed the survey, of whom 243/501 (49%) had evidence of carotid occlusive disease. On univariate analysis, smoking, hypertension, heart disease, hypercholesterolemia, diabetes, and stroke all correlated with greater than 50% carotid stenosis. Multivariate analysis indicated that snorers were significantly more likely to have carotid disease. Three hundred twenty‐seven participants were thought to have primary snoring. On univariate analysis, snorers were found to be significantly more likely to have carotid disease. After adjustment for covariates, snoring was not significant for carotid disease. However, multivariate analysis showed snorers to be significantly more likely to have bilateral carotid disease. Conclusions: This study shows a potential relationship between snoring and bilateral carotid artery stenosis greater than 50%; snorers have risk of carotid stenosis twice that of nonsnorers. Further investigation is warranted to better elucidate this relationship. Level of Evidence: 2b Laryngoscope, 129:265–268, 2019